Drivers of Home Health Nursing Profession - Ankit Singh1, Vivek Chaudhari1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: It is important to determine the perceived factors of home health nursing professionals whichare the drivers of home health nursing as a profession in developing countries.Objectives: To identify the variables driving the growth of the home care nursing profession.Methodology: Responses of 150 home health nursing professionals is processed with factor analysis.Result: Analysis reveals that the three factors together explained 45.6 percent variation in the data.Conclusion: The identified factors are “Comparative benefits over hospital care”, “Exclusive benefits ofhome healthcare”, and “Holistic view linking hospital care and home healthcare.”